2018
DOI: 10.1088/1361-6463/aab4be
|View full text |Cite
|
Sign up to set email alerts
|

Production of meloxicam suspension using pulsed laser ablation in liquid (PLAL) technique

Abstract: Production of organic particles in the micrometer/nanometer range can find applications in a wide range of areas, however for a number of materials it is not a straightforward task. In the present work pulsed laser ablation in liquid environment (PLAL) of meloxicam was studied aiming the production of near micrometer sized particles of this pharmaceutical ingredient. Targets pressed from crystalline meloxicam powder were placed in distilled water and irradiated with a focused beam of a frequency doubled (532 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
3
11
0
4
Order By: Relevance
“…The laminar, block-like and needle-shaped particles can be fractures of the pressed tablet, which preserved their solid state and retained the crystal structure ( Figure 7 ). The formation mechanism may be similar to that in a previously published experiment investigating nanosecond ablation in liquid [ 24 ]. In the current experiment, femtosecond laser irradiation induced fast material decomposition in a thin surface layer of the target, and the explosive expansion of the plasma plume that was created resulted in the formation of a shock wave.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The laminar, block-like and needle-shaped particles can be fractures of the pressed tablet, which preserved their solid state and retained the crystal structure ( Figure 7 ). The formation mechanism may be similar to that in a previously published experiment investigating nanosecond ablation in liquid [ 24 ]. In the current experiment, femtosecond laser irradiation induced fast material decomposition in a thin surface layer of the target, and the explosive expansion of the plasma plume that was created resulted in the formation of a shock wave.…”
Section: Discussionsupporting
confidence: 73%
“…Particle size reduction (and thereby improvement in the surface to volume ratio) is a possible way to enhance the dissolution rate, transport characteristics and bioavailability of these drugs [ 15 , 16 ]. Size reduction can be achieved by different approaches [ 17 , 18 ], such as forming solid dispersions [ 19 ], grinding [ 20 ], wet milling [ 21 ], cavitation [ 22 ], and laser ablation [ 11 , 12 , 13 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Laser ablation as a simple, rapid, easily adjustable and chemical-free method has received considerable attention in drug preformulation.…”
Section: Introductionmentioning
confidence: 99%
“…12) where submicron sized particle ejection occurs at nanosecond and few microsecond time scales. Larger, micron-sized and irregularly shaped particles are ejected in the microsecond scale [16][17][18][19] . The above observations apply mainly to homogeneous bulk materials.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that PLA/PLD is suitable for the size reduction of pharmaceutical particles without causing any chemical decomposition. In recent years, researchers have also started to use lasers for particle size reduction in drugs in liquid environment (PLAL) 18 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation